Copper-Catalyzed Alkynylation of Benzylic C–H Bonds with Alkynylboronic Esters - Buendia, Mikkel B.; Balin, Jan-Georges J.; Andersen, Mette E.; Lian, Zhong; Kramer, Søren (Synlett, 2021)
We report a simple method for copper-catalyzed benzylic C–H alkynylation that uses alkynylboronic esters as nucleophilic coupling partners. The catalytic system is readily available and the reaction takes place under mild conditions. Different substrates for the C–H functionalization, as well as various alkynylboronic ester nucleophiles, were evaluated. Finally, three examples of enantioselective C–H alkynylations are presented.
Keywords: C–H functionalization; copper catalysis; alkynylation; boronic esters; homogeneous catalysis